The Construction of a State of Knowledge on Professional Values in Mexico - Ana Hirsch Adler (Universidad Autónoma de Baja California, 2006)
This article presents the state of knowledge on professional values in Mexico and the elements that have allowed its construction, beginning in 2001. This is a meaningful, open-ended task, which grows as it is enriched by the addition of new-found research relevant to the study topic. There is described the process of the article's preparation, which took into account six types of resources: two anthologies from which were taken the chapters related to professional values; a state of knowledge produced by the Mexican Council of Educational Research, dedicated to research in this field; some articles from the online journalReencuentro's special issue on ethics; an anthology on values and moral development in education; and research reports on professional ethics and graduate thesis, not included in the five publications mentioned above. The construction of states of knowledge is considered to be greatly useful for the discussion of new research projects, and for supporting the development for those in process.